Enhanced dispersion of hydroxyapatite whisker in orthopedics 3D printing resin with improved mechanical performance. Issue 33 (14th April 2021) - Chong, Yi Ting; Tan, Clara S. H.; Liu, Li Ying; Liu, Jinyan; Teng, Choon Peng; Wang, FuKe
Abstract: One‐dimensional fillers such as rods and fibers have shown effective mechanical reinforcement in polymer nanocomposites, but their application in vat polymerization‐based 3D printing techniques was hindered due to the rapidly increased viscosity of the resin. In order to improve the fluidity of the composites without sacrificing the mechanical performance, herein we demonstrated that one‐dimensional hydroxyapatite (HAP) whiskers could be surface modified with 3‐(trimethoxysilyl) propyl methacrylate, to decrease the viscosity of the resulting resins and to enhance the interfacial adhesion between the filler and matrix. Rheology results showed that the resin was still fluidic with loading of HAP whiskers up to 20 wt%, with Young's modulus increased by a factor of 98% and the ultimate tensile strength increased by 26%. Successful printing of the resin on a DLP printer was achieved with high resolution and fine surface, and the biocompatibility test showed an increase in cell viability with the addition of HAP whiskers. These results provide a promising approach to develop high‐performance printable resin for orthopedic and related bio‐printing. Abstract : The present work demonstrated that surface modification of one‐dimensional hydroxyapatite (HAP) whiskers could help to not only decrease the viscosity of the 3D printing resins but also enhance the interfacial interaction.